Pengaruh Structural Assurance Dan Trust Terhadap Online Purchase Intention Pada Sistem Penjualan E–Commerce Perusahaan Xyz - ., Safri; ., Iswandir (Universitas Dirgantara Marsekal Suryadarma, 2023)
The Covid-19 pandemic has made the digital era develop rapidly, as well as e-commerce, the purchase process can be done from home, digital marketplace media facilitate users with interactive applications that can be called very responsive. PT XYZ, which usually conducts transactions in a traditional way, also has to keep up with developments. However, there are problems with the level of security and customer trust in e-commerce transactions. From the company's graphic data, it shows that customer loyalty has not been well developed.From the Structural Assurance variable at PT XYZ, where thitung is greater than ttable 5.315 > 1.667, due to the response from the sales admin who is very responsive to questions from customers from the Trust variable thitung is greater than ttable 2.816 > 1.667, needs to be improved, socialization about the company through digital media such as the web and non-digital media such as offline stores. From the simultaneous test, Fhitung is greater than Ftable 13.652 > 3.130. This shows that there is a significant influence of Structure Assurance and Trust together on Online Purchase Intention at PT XYZ